Protective effect of HLA-B57 on HCV genotype 2 infection in a West African population. - Chuang, W; Sarkodie, F; Brown, C; Owusu-Ofori, S; Brown, J; Li, C; Navarrete, C; Klenerman, P; Allain, J (2007)
Recovery from Hepatitis C virus (HCV) infection is considered infrequent (<20%) in western populations but reaches 50% in West Africa where genotype 2 infection is predominant. To investigate the role of cellular immune responses and host genetics in this phenomenon, samples from 104 Ghanaian blood donors reactive with anti-HCV assays were collected between 2000 and 2005. HCV antibody was confirmed by Western blot using genotype 2 recombinant core, E2 and NS3 proteins. Viral load and genotype were determined. Samples were stratified into 37 chronic, 35 recovered infections and 32 false positive. Eighty-one percentage of subjects with chronic infection (RNA positive) carried genotype 2 HCV. Cellular immune response was investigated in 35 frozen peripheral blood mononuclear cell (PBMC) samples suitable for interferon-gamma ELISPOT assay. Twelve out of 24 confirmed recovered, 1 out of 5 chronically infected and none of the 6 false-positive controls reacted to recombinant proteins. HLA-A, -B and -DR types were determined by DNA methodology. HLA-B*57 was significantly more frequent in the group which had recovered from HCV infection compared with chronically infected subjects (P = 0.0053, OR = 8.02). In conclusion, it is hypothesized that the dominance of genotype 2 HCV strains may be an important factor explaining the high rate of recovery from HCV infections in Ghana via an efficient contribution of HLA-B*57 which is relatively frequent in the population.